The Effect of GeoGebra- Assisted Learning Cycle 7e Model and Cognitive Style on the Mathematical Concepts Understanding Ability - Widyawati, Santi; Putra, Fredi Ganda; Bistari, B; Hamdani, H (IndoMath: Indonesia Mathematics Education, 2021)
This study aims to see the effect of: 1) cognitive style (Field Independent and Field Dependent) on the ability to understand mathematical concepts; 2) application of the geogebra-assisted cycle 7e learning model on the ability to understand mathematical concepts; 3) the interaction between the learning model group (learning cycle 7E learning model, learning cycle learning model 7E assisted by geogebra and conventional learning model) and the cognitive style group on students' mathematical concept understanding abilities. Quasi experimental design is used as a research method with data collection techniques using concept understanding tests and cognitive style tests. The two-way ANOVA test was used to find answers to the research objectives that had previously been tested for normality and homogeneity tests. Based on the test results, it can be concluded that: 1) The application of the 7E learning cycle learning model with geogebra has a good effect on the ability to understand mathematical concepts; 2) cognitive style has no effect on mathematical understanding ability; and 3) there is no interaction between the learning model group and the cognitive style group on the ability to understand mathematical concepts.